(untitled) (El-Wahat Journal for Research and Studies, 2023)
Abstract: This study is concerned with the analysis of the oral communication needs for Algerian employees at business workplace. The study adopts the quantitative approach in which the data were collected through a questionnaire which was distributed to (20) employees. The main results showed that most of the employees faced problems in the oral language communication aspects such as pronunciation, oral presentation, and negotiations. On the basis of the results, pedagogical recommendations are suggested for English Foreign language instructors to focus on the relevant business English oral communication skills and needs. Keywords: Communication needs, communication skills, business English, English for specific purposes, needs analysis, speaking performance. ملخص: اهتمت هذه الدراسة بتحليل احتياجات التواصل الشفهي للموظفين الجزائريين للعمل التجاري. الهدف الرئيسي من الدراسة الحالية هو تحليل الاحتياجات الشفوية للتواصل الوظيفي للموظفين في شركة "سيفيتال" بمدينة بجاية. اعتمدت الدراسة على المنهج الكمي أين جُمعت البيانات من خلال استبيان تم توزيعه على (20) موظفاً. أظهرت النتائج الرئيسية أن معظم الموظفين يواجهون مشاكل في معظم المهارات اللغوية أثناء التواصل مع الأجانب مثل النطق، والعروض التقديمية الشفوية، والاجتماعات، وايصال المهام والواجبات اليومية. على أساس النتائج تم اقتراح توصيات تربوية للأساتذة والطلاب للتركيز أكثر على احتياجات ومهارات الاتصال الشفوي باللغة الإنجليزية للأعمال ذات الصلة. كلمات دالة: اللغة الإنجليزية لأغراض محددة، اللغة الإنجليزية للأعمال، تحليل الاحتياجات، احتياجات الاتصال، مهارات الاتصال، أداء التحدث.